Improving access to contraception through integration of family planning services into a multidrug-resistant tuberculosis treatment programme. Issue 2 (27th November 2019) - Cornish, Emily F; Hudson, Jonathan; Sayers, Ross; Loveday, Marian
Abstract : Objectives: Multidrug-resistant tuberculosis (MDR-TB) is a global public health priority. The advent of the World Health Organisation's Short Course regimen for MDR-TB, which halves treatment duration, has transformed outcomes and treatment acceptability for affected patients. Bedaquiline, a cornerstone of the Short Course regimen, has unknown teratogenicity and the WHO therefore recommends reliable contraception for all female MDR-TB patients in order to secure eligibility for bedaquiline. We were concerned that low contraceptive uptake among female patients in our rural South African MDR-TB treatment programme could jeopardise their access to bedaquiline. We therefore conducted a service delivery improvement project that aimed to audit contraceptive use in female MDR-TB patients, integrate family planning services into MDR-TB care, and increase the proportion of female patients eligible for bedaquiline therapy. Methods: Contraceptive use and pregnancy rates were audited in all female patients aged 13–50 years initiated on our MDR-TB treatment programme in 2016. We then implemented an intervention consisting of procurement of depot-medroxyprogesterone acetate (DMPA) for the MDR-TB unit and training of specialist MDR-TB nurses in administration of DMPA. The audit cycle was repeated for all female patients aged 13–50 years initiated on the programme in January–October 2017 (post-intervention). Results: The proportion of women on injectable contraceptives by the time of MDR-TB treatment initiation increased significantly in the post-intervention cohort (77.4% vs 23.9%, p<0.0001). Conclusion: By integrating contraceptive services into our MDR-TB programme we significantly increased contraceptive uptake, protecting women from the obstetric risks associated with pregnancy during MDR-TB treatment and maximising their eligibility for bedaquiline therapy.